Transmitiendo el Sentido Común: Los Cánticos y el Comportamiento Colectivo - Pozzi, Pablo A. (Trabalhos de Antropologia e Etnologia, 2020)
Argentina has a long tradition of political and football slogans. Most analysts consider that there is a strong linkage between both. These slogans are designed to be chanted by hundreds and thousands of voices in political mobilizations and in football stadiums. This paper focuses on political chants. This paper attempts to delve, through the study of a series of political chants and slogans, the persistence of a left-wing political subjectivity throughout 20th Century Argentina. At the same time, it seeks to link these chants with specific figures of speech that appear in the testimonies of political activists.